Taxpayer Compliance based on Social Norm and Tax Moral - Anggraeni, Windi Ariesti; Ningsih, Winda; Romdhon, Mochamad (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2023)
This research aims to analyze the role of social norm and tax moral in influencing tax compliance among Micro, Small, and Medium Enterprises (MSMEs). MSMEs hold significant potential as a tax source for the government due to their vital contribution to the economy. In this study, the Theory of Planned Behavior serves as the foundational framework to explore the impact of social norms and morality on tax compliance among MSMEs. Primary data was collected from 100 MSME respondents registered as taxpayers through a survey method, and multiple regression analysis was employed to test hypotheses. The discussion that focuses on the influence of social and moral norms on the tax compliance of MSME taxpayers is a novelty in this research and has not been extensively explored before. The research findings indicate that both social norms and morality significantly influence the level of tax compliance among MSMEs. These results offer valuable insights for the government and stakeholders in crafting more effective tax policies to enhance tax revenue from the MSME sector and support overall economic growth.